Understanding Indonesian Indigenous Leadership in Higher Education: A Study of Islamic and Hindu-Based Universities - Kultsum, Ummi; Swastini, Ni Komang Arie; Mahardika, I Gusti Ngurah Agung Wijaya (Muslim Education Review, 2023)
This study examined how Islam and Hinduism influence leadership practices in religion-based higher education institutions. Exploration studies were conducted in two areas, Tangerang and Bali. Eight participants were interviewed, including vice deans and heads of departments. The research findings revealed that cultural and spiritual values in leadership are deeply embedded in their character. The values, such as spirituality and trust, emerge as crucial essential traits within friendly relations. Likewise, leadership characteristics manifest in Hindu concepts that display religious values. Concepts such as Karmapala, Swadarma, and Karma Dharma Yoga strongly connect with Islamic values where being a leader is considered God's Trust (amanah) and fulfilling leadership responsibilities is considered an act of worship (Ibadah).